Role of Lycopene in the Management of Oral Submucous Fibrosis (Medical Forum Monthly, 2023)
Objective: To evaluate the efficacy of lycopene in treatment of oral submucosal fibrosis in combination with intralesional steroids.Study Design: A Cross sectional studyPlace and Duration of Study: This study was conducted at the Oral and Maxillofacial Surgery, Bibi Aseefa Dental College, Shaheed Mohtarma Benazir Bhutto Medical University, Larkana, Sindh from March 2022 to February 2023.Materials and Methods: A total of 399 patients with habit of chewing areca nut in the form of Gutka, Mawa, Pan Masala or in the pure form were enrolled and divided into three groups by their treatment plan. SPSS version 24 was used for data analysis. Burning sensation in form of VAS score and mouth opening were variables of study.Results: Gutka was the most common used areca nut as 255 (63.9%). The average duration of habit was 5.08±2.03 years. Whereas, the overall average VAS scores of the patients was 7.08±1.78. Mouth opening from baseline and treatment period among the groups A, B and C was 3.88±1.69, 2.99±1.58 and 2.64±1.42 respectively.Conclusion: Lycopene combined with hyaluronidase and intralesional steroid is effective in improving pain (VAS) and symptoms of mouth opening in patients with OSF with no side effects.